2017
DOI: 10.1016/j.molimm.2017.05.029
|View full text |Cite
|
Sign up to set email alerts
|

SALSA—A dance on a slippery floor with changing partners

Abstract: It is becoming increasingly clear that the connections between our immune system and the microbiota colonizing us have a tremendous impact on human health. A number of innate molecular defence mechanisms cooperate to selectively target unwanted microorganisms at the mucosal surfaces. Amongst others these include the complement system, IgA and the SALSA molecule. The salivary scavenger and agglutinin (SALSA), also known as deleted in malignant brain tumors 1 (DMBT1), salivary agglutinin (SAG) or gp340 is a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 145 publications
(255 reference statements)
1
65
0
Order By: Relevance
“…In the present study, we demonstrated that HAECs produced and released DMBT1 in response to stimulation with S. mutans. DMBT1 has been shown to be expressed in various epithelial and non-epithelial tissue types (Reichhardt et al, 2017). At mucosal surfaces, DMBT1…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we demonstrated that HAECs produced and released DMBT1 in response to stimulation with S. mutans. DMBT1 has been shown to be expressed in various epithelial and non-epithelial tissue types (Reichhardt et al, 2017). At mucosal surfaces, DMBT1…”
Section: Discussionmentioning
confidence: 99%
“…DMBT1 (deleted in malignant brain tumors 1), also known as salivary agglutinin (Ericson & Rundegren, ) or gp‐340 (Holmskov et al, ), belongs to the scavenger receptor cysteine–rich superfamily and is expressed in epithelial and non‐epithelial tissues throughout the body (Osei, Deivanayagam, & Nichols, ; Reichhardt, Holmskov, & Meri, ). DMBT1 exists as two variants, namely, as secretory and cell–associated types, and the secretory type exists in two conformations, namely, in soluble and immobilized forms (Osei et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Salivary Scavenger and Agglutinin (SALSA), also known as gp340, ‘deleted in malignant brain tumors 1’ (DMBT1) and salivary agglutinin (SAG), is a multifunctional molecule found in high abundance on human mucosal surfaces [14]. SALSA has widespread functions in innate immunity, inflammation, epithelial homeostasis and tumour suppression [57]. SALSA binds and agglutinates a broad spectrum of pathogens including, but not limited to, human immunodeficiency virus type 1, Helicobacter pylori , Salmonella enterica serovar Typhimurium , and many types of streptococci [811].…”
Section: Introductionmentioning
confidence: 99%
“…The first 13 SRCRs are 109 amino acid (aa) domains found as “pearls on a string” separated by SRCR interspersed domains (SIDs) (Figure 1a) [1, 21]. The SIDs are 20-23 aa long stretches of predicted disorder containing a number of glycosylation sites which have been proposed to force them into an extended conformation of roughly 7 nm [7]. In addition to this main form, alternative splicing and copy number variation mechanisms lead to expression of variants of SALSA containing variable numbers of SRCRs in the N-terminal region.…”
Section: Introductionmentioning
confidence: 99%